Development and test of a portable device to monitor the health status of Sarda breed sheep by the measurement of the milk electrical conductivity. Issue 2 (2nd April 2016) - Caria, Maria; Chessa, Giovanni; Murgia, Lelia; Todde, Giuseppe; Pazzona, Antonio
Abstract: The electrical conductivity (EC) of milk is a parameter which is often used for identifying sub-clinical mastitis in dairy animals. It is widely used for cattle, and is measured either by means of probes integrated into the milking machine or by means of portable devices. However this is not the case for small ruminants, where the available devices are few. The aim of this study is to deepen the knowledge of about the relationship between EC and certain constituents of Sarda sheep milk, and thus to develop a portable device specifically designed for on-site measurement of conductivity and to estimate the somatic cell count (SCC) of Sarda sheep milk. Therefore, the device allows a rapid test for checking the acceptability of milk to monitor the effects of udder infection. The receiver operating characteristic (ROC) method was used to evaluate how efficacious EC was in discriminating between animals with a somatic cell level higher or lower of a threshold value previously defined. The cut-off values, sensitivity, specificity and the area under the ROC curve for EC were, respectively, 4.835 mS/cm, 73.08, 75.46 and 0.804, using a threshold of 700 000 cells/ml. Our results gave a positive evaluation of the portable device that we had designed for estimating the SCC in sheep milk. Only 8.8% of the samples were incorrectly identified as negative. A portable device for EC measurement is a useful tool for monitoring the somatic cell level individually, and allows early and efficacious action to contrast new intramammary infections.